2017
DOI: 10.2174/1568026617666170707123553
|View full text |Cite
|
Sign up to set email alerts
|

Arylurea Derivatives: A Class of Potential Cancer Targeting Agents

Abstract: Arylurea derivatives, an important class of small molecules, have received considerable attention in recent years due to their wide range of biological applications. Various molecular targeted agents with arylurea scaffold as potential enzyme/receptor inhibitors were constructed with the successful development of sorafenib and regorafenib. This review focuses on those arylureas possessing anti-cancer activities from 2010 to date. According to their different mechanisms of action, these arylureas are divided in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Pyridyl urea I c was also anti-proliferative, with some preference toward the melanoma and breast cancer cell line ( Figure 4 ). The observed activity was in line with the already described in the literature [ 29 ].…”
Section: Discussionsupporting
confidence: 92%
“…Pyridyl urea I c was also anti-proliferative, with some preference toward the melanoma and breast cancer cell line ( Figure 4 ). The observed activity was in line with the already described in the literature [ 29 ].…”
Section: Discussionsupporting
confidence: 92%
“…It has previously been reported that some proteins, including proliferating cell nuclear antigen (PCNA), Oct4 and hypoxia-inducible factor-1α (HIF-1α), which maintain stemness of cancer stem cells, are regulated by the small ubiquitin-like modifier (SUMO) pathway ( 19 - 25 ). Due to the extensive and important role of SUMOs, direct SUMO gene silencing often leads to the death of various cell types, particularly precursor cells that participate in tissue repair, which may lead to serious side effects ( 26 , 27 ).…”
Section: Introductionmentioning
confidence: 99%